Sociological Analysis of One’s Education - Wang, Leslie (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Reflect on your educational experience (schooling). This may be a particular school, a particular grade, a particular class, etc. (This may also include college.) Analyze your educational experience.